Analysis of the prevalence of systemic de novo thrombotic microangiopathy after ABO‐incompatible kidney transplantation and the associated risk factors. (6th October 2019) - Tasaki, Masayuki; Saito, Kazuhide; Nakagawa, Yuki; Imai, Naofumi; Ito, Yumi; Yoshida, Yutaka; Ikeda, Masahiro; Ishikawa, Shoko; Narita, Ichiei; Takahashi, Kota; Tomita, Yoshihiko
Abstract : Objectives: To analyze the prevalence of systemic de novo thrombotic microangiopathy in ABO‐incompatible kidney transplantation and risk factors associated with this condition. Methods: A total of 201 patients who received living‐donor kidney transplantation (114 patients with ABO‐identical kidney transplantation and 87 patients with ABO‐incompatible kidney transplantation) were retrospectively analyzed. Systemic de novo thrombotic microangiopathy was diagnosed clinically according to the presence of thrombocytopenia with microangiopathic hemolytic anemia and pathological findings of thrombotic microangiopathy. Anti‐A and anti‐B antibodies were purified from human plasma, and these antibodies' bindings to human kidney were investigated in vitro . Results: ABO‐incompatible kidney transplantation was a significant risk factor of systemic de novo thrombotic microangiopathy (odds ratio 55.9, 95% CI 1.8–8.9, P  < 0.001) after transplantation. Multivariate logistic regression analysis showed that non‐use of mycophenolate mofetil, pretreatment immunoglobulin G antibody titer ≥64‐fold and pretransplant immunoglobulin M antibody titer ≥16‐fold were significant risk factors for systemic de novo thrombotic microangiopathy in ABO‐incompatible kidney transplantation. Microvascular inflammation of 1‐h post‐transplant biopsy could be observed more frequently in thrombotic microangiopathy patients than in non‐thrombotic microangiopathy patients. Anti‐A and anti‐B antibodies purified from human plasma showed a strong in vitro reaction against human kidney when the antibody titer was ≥16‐fold. Conclusions: Antibody titer should be decreased to ≤16‐fold until the day of ABO‐incompatible kidney transplantation by desensitization therapy including mycophenolate mofetil. The 1‐h biopsy results might help to diagnose systemic de novo thrombotic microangiopathy.